2015
DOI: 10.1111/jace.13642
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis, Sintering and Piezoelectric Properties of Ba0.85Ca0.15 Zr0.1Ti0.9O3 Lead‐Free Ceramics

Abstract: The preparation of Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 (BCZT) powders by wet chemical methods has been investigated, and the powders used to explore relationships between the microstructure and piezoelectric properties (d 33 coefficient) of sintered BCZT ceramics. Sol-gel synthesis has been shown to be a successful method for the preparation of BCZT nanopowders with a pure tetragonal perovskite phase structure, specific surface area up to 21.8 m 2 /g and a mean particle size of 48 nm. These powders were suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…The poled ceramic shows a bulk d 33 around 232 pC/N. This value is comparable with the bulk d 33 obtained by A. Reyes et al 6 and K. Castkova et al 41 . The local piezo-response and the macroscopic ferroelectric behavior observed in this sample is in agreement with the global tetragonal structure formed, as it can be observed in the XRD 2D-GIXRD and Raman sections.…”
Section: Panel (A) Insupporting
confidence: 79%
“…The poled ceramic shows a bulk d 33 around 232 pC/N. This value is comparable with the bulk d 33 obtained by A. Reyes et al 6 and K. Castkova et al 41 . The local piezo-response and the macroscopic ferroelectric behavior observed in this sample is in agreement with the global tetragonal structure formed, as it can be observed in the XRD 2D-GIXRD and Raman sections.…”
Section: Panel (A) Insupporting
confidence: 79%
“…3 for multi-component compounds such as BCZT that involves several precursors, this is highly demanding. Nonetheless, synthesis of BCZT using various wet chemical synthesis techniques including Pechini polymeric precursor method and hydrothermal process have been tried in the past [10][11][12][13][14][15][16]. However, neither comparison, nor deep investigation into the grain size effect in both types of ceramics have been undertaken so far.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It may not be out of place to mention that a few previous reports on comparative studies are available in literature [14,15], which explore relationships between the sintering conditions and only piezoelectric properties of these materials. Present work, on the other hand, provides a comprehensive study correlating the effect of grain size on various other electrical properties as well.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This improvement in d 33 and k p could be attributed to the formation of the O-T phase boundary because there are more polarization states involved when near room temperature. In addition, oxygen vacancies should be mainly responsible for the substitution of Nb 5+ ions on the B-site(Ti 4+ )because of the migration of oxygen vacancies, and because of the interaction between defect dipoles and spontaneous polarization inside the domains[26][27][28]. The d 33 and k p values in this study are much higher than those reported for BCZT-xABO 3 ceramics[9- 11], but they did decrease with an increase in CBN content.…”
mentioning
confidence: 99%